Literasi Pemberdayaan Ekonomi Kaum Perempuan Nahdliyin (NU) Melalui Phygital Marketing Di Kabupaten Kebumen - Baehaqi, Muhammad; Rizana, Dani; Ahmad Syarifudin; Anton Prasetyo; Awaludin Abid; Eko Wardoyo (JCSE: Journal of Community Service and Empowerment, 2024)
The aim of this service is to provide assistance and facilitation to Nahdliyin women business actors so that they have independence and business skills. Providing enforcement of the informal sector as an advanced, competitive and productive business entity, as well as mobilizing the potential of existing resources as a community business force that can support the family economy. Devotion answers existing problems such as limited resources, existing business, product limitations and limited market reach. Service is carried out using a participatory method by placing partners as holders of a more dominant role. The service begins with training, then a business cluster is formed and the formation of business entities is facilitated for partners.